Post-pandemic echoes in the forms of spending and organizing leisure time by the Polish people - Kolny, Beata (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article explores the extent to which various leisure activities adopted during the pandemic, due to the closure of service facilities and other restrictions, are still popular among individuals. It draws on both secondary research and primary data collected through a website survey technique among 1,100 adult Poles in November 2022. The findings indicate that Poles continue to enjoy streaming movies and music, and maintain social connections online even after the pandemic. Those who used physical activity tracking apps during the pandemic still rely on them. Due to travel restrictions and uncertainty of the pandemic period, respondents now plan and book trips within Poland on short notice.
Keywords: leisure time; consequences of the COVID-19 pandemic; consumer